Earnings and Investment Differentials Between Migrants and Natives: A Study of Female Street Vendors in Bengaluru City. (March 2021) - Kambara, Channamma; Bairagya, Indrajit
This article explores whether there exists any difference in the earnings of self-employed migrant and native street vendors in a metro city, and if so, in what ways this difference is prominent. In order to accomplish the objective, we have collected data from women street vendors from Bengaluru city. The results depict that although there is no significant difference in the earnings between native and migrant street vendors, a significant difference exists in the size of investments made by them, that is, to earn the same amount of income, migrants need to invest more than natives. Moreover, the results, based on the Oaxaca–Blinder decomposition method, indicate that the pre-labour market endowment factors do not make a significant contribution to the overall difference in the rate of returns. The difference, instead, mainly exists because of the coefficient differences, which can be attributed to discrimination.